Bir şerh dört şârih: Eşrefoğlu’nun Kasîde-i Hayrân şiirinin şerhleri ve bu şerhlerin aidiyeti meselesi - (:unkn) unknown (My University, 2012)
Şerh edebiyatı, dinî tasavvufî Türk edebiyatı ürünleri arasında mühim bir yer tutmaktadır. En çok şerh edilen metinler, hususi bir dil ile söylenen ve şathiye olarak isimlendirilen şiirlerdir. XV. asrın mühim sûfî şâirlerinden olan Eşrefoğlu Rûmî’nin “Kasîde-i Hayrân” ismiyle tanınan şiiri de bir şathiyedir. Bu zamana kadar Abdullah Salâhî-i Uşşâkî tarafından şerh edildiğini bildiğimiz bu şiirin başka şârihleri de olduğu tespit edilmiş, fakat sadece bir şerh metnine ulaşılmıştır. Bu makale Eşrefoğlu’nun şiirine şerh yazan müellifin kim olduğu sorusuna cevap aramaktadır.

Commentary (sharh) literature has a significant place in the Turkish religiousmystic literature. The most interpreted texts are the ones called shathiyyah, which are written based on a special style. “Qaside-i Hayran” written by Eshrefoglu Rumi, one of the most prominent Sufi poets of XVth century, is a shathiyyah. It has been known that there were other commentaries written about this poem which was known as glossed by Abdullah Salahî, however so far only one of those commentaries has been discovered. This article searches for answer to the question of the identity of sole commentator of Eshrefoglu’s poem.
One commentary four commentators: Commentaries of Eshrefoglu Rumi’s Qasîda-i Hayrân and the question of the authorship of these commentaries
Keywords: Din Bilimi